Injury elicited increase in spinal cord neurosteroid content analysed by gas chromatography mass espectrometry - Labombarda, Maria Florencia (2006)
The effects of spinal cord injury (SCI), combined with castration and adrenalectomy, and of progesterone (PROG) treatment on neurosteroid levels and steroidogenic enzyme expression were investigated in the adult male rat spinal cord (SC). Steroid levels were quantified by gas chromatography/mass spectrometry in SC and plasma, and mRNAs of enzymes by quantitative real-time RT-PCR. The levels of pregnenolone (PREG), PROG, 5alpha-dihydroprogesterone, 3alpha,5alpha-tetrahydroprogesterone increased in SC 75 h after transection without significant increase in the plasma. After combined adrenalectomy and gonadectomy, significant levels of PREG and PROG remained in the SC, suggesting their local biosynthesis. In the SC of adrenalectomized and gonadectomized rats, there was an increase of PREG 24 h after SCI, followed at 75 h by a concomitant increase in its direct metabolite, PROG. These observations are consistent with a sequential increase of PREG biosynthesis and its conversion to PROG within the SC in response to injury. However, no significant change in P450-side chain cleavage and 3beta-hydroxysteroid dehydrogenase/Delta5-Delta4 isomerase mRNA levels was observed after SCI. Systemic PROG treatment after SCI, resulted in a very large increase in PROG, 5alpha-dihydroprogesterone, and 3alpha,5alpha-tetrahydroprogesterone in both plasma and SC. Furthermore, high levels of 3beta,5alpha-tetrahydroprogesterone were detected in SC, whereas their plasma levels remained barely detectable. Because the ratio of reduced metabolites to PROG was 65-times higher in SC than in the plasma, it appears likely that reduced metabolites mainly originated from local biosynthesis. Our results strongly suggest an important role for locally biosynthesized neurosteroids in the response of the SC to injury.